Behind an intern’s eyes:Thoughts on Internship Program in Nepal - Gelal, Dharana; Mishra, Aavash (Journal of Karnali Academy of Health Sciences, 2022)
Internship acts as a bridge to complete the void between the years of learning and putting it into actual practice and serves to gear up the graduates with relevant clinical skills, experience, and knowledge. Furthermore, internship serves to gear up the graduates with relevant clinical skills, experience, and knowledge that they will be required to perform on a day-to-day basis when they go ahead with their professional careers. One of the key issues that has been voiced frequently in numerous platforms of Nepal seems to be the stipend currently provided to the interns by the hospital management. Even though universities have laid out their description of their internship program, the job description of interns still remains vague in a hospital setting, which has led interns into doing work that does not fulfill the learning objectives of internship at all and has allowed hospitals to employ interns in various settings overlooking their working hours and limits. The culture of making interns and residents work for unaccountable hours in the name of learning suits the hospital management and ultimately lessens their need to hire skilled professionals, creating another set of unemployment problems down the road. There is also an increased incidence of depression, anxiety, fatigue, and panic attacks among interns, and it is very important for senior professionals and hospital management to address them in time by creating a positive and encouraging work environment, accessibility to support groups, and restricting work hours.